188k views
3 votes
The functions h(x) and g(x) are defined as h(x)= ¹⁰/x -3 and g(x)=3x-2evaluate hg(4)

1 Answer

4 votes

We will use the property


(fg)(x)=f(x)g(x)

Given data:

It is given that


h(x)=(10)/(x)-3,g(x)=3x-2_{}

Now,


\begin{gathered} hg(x)=h(x)g(x) \\ =((10)/(x)-3)(3x-2) \\ =(10)/(x)(3x-2)-3(3x-2) \\ =30-(20)/(x)-9x+6 \\ =36-(20)/(x)-9x \end{gathered}

Now hg(4) will be


\begin{gathered} hg(4)=36-(20)/(4)-9(4) \\ =36-5-36 \\ =-5 \end{gathered}

So, the required answer is -5.

User Webbyfox
by
5.5k points